Data for: Wolves make roadways safer, generating large economic returns to predator conservation ... - Raynor, Jennifer; Grainger, Corbett; Parker, Dominic (Dryad, 2021)
This dataset includes information on deer-vehicle collisions, vehicle miles traveled, weather, and deer, wolf, and human populations, for counties in Wisconsin from 1981-2016. ... : These data are described in the README.txt file. A full replication package for the paper associated with this data is available at: https://github.com/jennifer-raynor/wolvs_and_DVCs. ...